2003
DOI: 10.1143/jjap.42.2564
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Initial Rapid Decay on Light-Induced Carrier Lifetime and Cell Performance Degradation of Czochralski-Grown Silicon

Abstract: The rapid initial degradation of Czochralski-grown silicon (Cz-Si) solar cell performance has been investigated. The initial rapid degradation occurs at the beginning of the degradation process and is followed by a second slower degradation. The surface effect due to interface state degradation between the passivation layer and the Si substrate was investigated on several kinds of Cz-and float zone Si (FZ-Si) wafers. Carrier lifetime degradation induced by an illumination for 30 s was observed on every Cz-Si w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Another process where boron–oxygen interaction plays an important role is the light‐induced degradation of Si solar cells. This process is characterized by much lower activation energies, one initial fast process with an activation energy around 0.2 eV followed by a slow degradation process with activation energies between 0.4 and 0.5 eV . It was suggested that the degradation is associated with the formation of boron–oxygen dimer centers (B i O 2i or B s O 2i ) .…”
Section: Introductionmentioning
confidence: 99%
“…Another process where boron–oxygen interaction plays an important role is the light‐induced degradation of Si solar cells. This process is characterized by much lower activation energies, one initial fast process with an activation energy around 0.2 eV followed by a slow degradation process with activation energies between 0.4 and 0.5 eV . It was suggested that the degradation is associated with the formation of boron–oxygen dimer centers (B i O 2i or B s O 2i ) .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the ξ(C i O i + ) is nearly identical to the ξ(O 2i + ) since the similar charged supercells should have the similar defect-defect interactions in the CASTEP code, then the ξ term can be offset in MM calculation as shown in Eq. (4). So the energy levels of O 2i and B s O 2i with better accuracy can be expected by using the marker method.…”
Section: Structuresmentioning
confidence: 98%
“…Light-induced degradation (LID) has received considerable attention in recent years due to its detrimental impact on the performance of photovoltaic (PV) solar cells under field conditions [1]. Several studies investigating this effect have been published and introduced various trends and interpretations [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. LID phenomenon was firstly presented in 1973 by Fischer and Pschunder [2]; they observed a significant degradation of the efficiency of Cz-based silicon solar cells under illumination.…”
Section: Introductionmentioning
confidence: 99%